PENGARUH MEDIA VIDEO TERHADAP TINGKAT PENGETAHUAN REMAJA PUTRI TENTANG PEMERIKSAAN PAYUDARA SENDIRI (SADARI) DI KABUPATEN KUPANG PROVINSI NUSA TENGGARA TIMUR - Maya Lavenia Serna; Fitri Handayani; Maria Agustina Making; Riny Pujiyanti; Antonia Helena Hamu (Journal of Innovation Research and Knowledge, 2025)
Breast cancer is one of the most common cancers in women and can be prevented or treated early through early detection. It is important to introduce breast self-examination (SADARI) as early as adolescence to increase awareness of changes in the breast and encourage healthy living behaviors early on. Objective: To analyze the effect of video media on the level of knowledge of adolescent girls about breast self-examination (SADARI) at SMAN 1 Taebenu, Kupang Regency. Methods: This study is a quantitative research with pre-experiment research design with one group pre-post test design without control group. The sample size was 76 respondents. This research was conducted at SMAN 1 Taebenu, Kupang Regency, East Nusa Tenggara Province. The sampling technique used was stratified random sampling and analysis using the Wilcoxon test. Results: There is an effect of video media on the level of knowledge of adolescent girls about breast self-examination (SADARI) in adolescent girls at SMAN 1 Taebenu, Kupang Regency. after being given education with video media about SADARI, there was an increase in the knowledge of 72 respondents in the good category (95%), while as many as 4 people (5%) were in the category of moderate knowledge level. Respondents who have sufficient knowledge about SADARI after being given education with video media, due to various factors, one of which is that respondents do not pay good attention when given education